2022
DOI: 10.1016/j.ajic.2022.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Risk of COVID-19 in healthcare workers working in intensive care setting

Abstract: Background The higher risk of COVID-19 in healthcare workers (HCWs) is well-known. However, the risk within HCWs is not fully understood. The objective was to compare the COVID-19 risk in intensive care unit (ICU) versus non-ICU locations. Methods A prospective surveillance study was conducted among HCWs at a large tertiary care facility in Riyadh between March 1st to November 30th, 2020. HCWs included both clinical (provide direct patient care) and non-clinical positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In line with a few previous studies, we found that non-caregivers in contact with patients and/or caregivers (notably staff in radiology, functional assessment and stretcher services) had a higher risk of COVID-19 than other staff [14,32,33]. Indeed, staff can be exposed to SARS-CoV-2 before the infected patient has received a firm diagnosis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with a few previous studies, we found that non-caregivers in contact with patients and/or caregivers (notably staff in radiology, functional assessment and stretcher services) had a higher risk of COVID-19 than other staff [14,32,33]. Indeed, staff can be exposed to SARS-CoV-2 before the infected patient has received a firm diagnosis.…”
Section: Discussionsupporting
confidence: 91%
“…More than half of the cases of COVID-19 (56.8%) were probably hospital-acquired. This rate is higher than those previously reported in the literature (ranging from 25% to 48%) on the basis of self-reported infections [9,10,14,26]. Several studies found that exposure in a community setting was the greatest risk factor [27], and recent studies with genotyping data have shown that the community is the main source of SARS-CoV2 infection [3][4][5].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The clinical management of these patients represents a great challenge for healthcare workers, especially when treatments involve exposure to saliva and/or blood. A fact that places them at greater risk of contamination and virus transmission [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining a 12‐lead ECG typically involves additional nursing staff being exposed to equipment fitted with numerous ECG wires, heightening the risk of contagious disease transmission. KM1L offers several benefits, including ease of use (patients can be instructed to operate it, reducing contact with healthcare personnel), remote data transmission (thus reducing the risk of contamination), compact size, and easy disinfection (Alshamrani et al., 2022 ; Chu et al., 2020 ; González et al., 2020 ; Klompas et al., 2021 ; Zaballos et al., 2023 ). In hospitalized patients, comparisons with a standard 12‐L ECG demonstrate the KM1L device's noteworthy numerical accuracy and exceptional agreement in identifying QTc prolongation (Marín et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%